Intraventricular Hemorrhage and Cognition - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The effects of premature birth-related subependymal and mild intraventricular hemorrhage (S/IVH) on specific cognitive abilities in 2-year-old children were investigated at the Perinatology Center, New York Hospital, and Cornell and New York University Medical Colleges.